Green Leadership as a Model of Effective Leadership in Hospital Management in the New Normal Era - Mikaria Gultom (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The Covid-19 pandemic that has hit humanity throughout the world has become a very serious and very scary problem at least in the last two years since the end of 2019. Hospitals as health service institutions are also experiencing difficulties and are overwhelmed by the surge of patients who need treatment as well as health workers who participate exposed to the Covid-19 virus. Hospital management is very unprepared for this tremendous change, both in patient handling, labor management, changes in patient service flow, health insurance and workforce safety as well as the management of a very high spike in medical and non-medical waste. Against this unsettled situation, green leadership offers a solution to the difficulties experienced by the hospital business through effective leadership strategies during this pandemic. This research is a literature review, both from the facts on the ground in Indonesian hospitals during the COVID-19 pandemic and the views of experts about the importance of green leadership for hospitals facing the possibility of external extreme turbulence such as the current pandemic while still paying attention to the balance of the ecosystem and its environment. The findings of this study contribute to green leadership strategy in the management of hospital services in the new normal era.